Acute and severe acne in a patient treated with bevacizumab. (22nd February 2013) - Molina‐Ruiz, Ana María; Domine, Manuel; Requena, Luis
Abstract: Background  Bevacizumab is a recombinant, humanized monoclonal antibody against vascular endothelial growth factor (VEGF) that inhibits angiogenesis. Bevacizumab is typically well tolerated; its major side effects include hypertension, proteinuria, bleeding, gastrointestinal perforation, and arterial thrombotic events, among others. Cutaneous side effects associated with the use of bevacizumab are rare and involve mainly itching and exfoliative dermatitis. Nonspecific skin rash and acneiform eruptions have recently been described in patients following infusion of bevacizumab. Methods  Findings in a 52‐year‐old patient with stage IV lung cancer with brain metastasis, who developed severe, acute, and persistent acne after intravenous (IV) infusion of bevacizumab, are examined. Results  The cutaneous eruption was classified as true acne rather than as an acneiform eruption because all cutaneous lesions of acne, namely comedones, inflammatory papules, and pustules, were present. Conclusions  To the authors' knowledge, this is the first report of an association between acne and IV administration of bevacizumab.